Application of crisis management in patient complaint management in the pediatric dentistry clinic (危机管理在儿童口腔门诊投诉管理中的应用) - ZHOU Lina (周莉娜); LUO Sha (罗莎); WANG Yan (王雁) (中西医结合护理, 2023)
Objective To investigate the effect of crisis management in patient complaint management in the pediatric dentistry clinic. Methods Totally 200 cases of pediatric patients who visited the pediatric dentistry clinic between January and December 2021 were included as the control group, and routine nursing management was carried out during the treatment. Another 200 cases of pediatric patients who visited the pediatric dentistry clinic between January and December 2022 were recruited as the study group, and a crisis management model was adopted. The complaint rate, praise rate and satisfaction with nursing service were measured and compared between two groups. Results The complaint rate in the study group was lower than that in the control group (1. 00% vs. 5. 50%, P＜0. 05). The praise rate in the study group was higher than that in the control group (12. 00% vs. 4. 50%, P＜0. 01). The rate of satisfaction with working attitude, humanistic care, clinic procedure, health education and overall satisfaction rate in the study group were higher than those in the control group(P＜0. 05). Conclusion The crisis management is effective to reduce the rate of patient complaint and improve the nursing quality in the pediatric dentistry clinic. It is an effective strategy to facilitate the healthy and stable development of pediatric dentistry clinic (目的 探讨危机管理理论在儿童口腔科门诊患者投诉管理中的应用效果。方法 选取2021年1月—12月就诊于儿童口腔科的200例患儿为对照组, 实施常规护理管理; 2022年1月—12月就诊的200例患儿为研究组, 实施危机管理。对比实施危机管理前后护理投诉发生率、表扬率以及患儿家属满意度。结果 实施护理危机管理后, 研究组护理投诉率1. 00%(2/200), 较对照组5. 50%(11/200)降低, 差异有统计学意义(P＜0. 05)。研究组受到患儿家属表扬24(12. 00%)人次, 较对照组9(4. 50%)人次上升, 差异有统计学意义(P＜0. 01)。工作态度、人文关怀、就诊流程、健康教育及总满意评价研究组均高于对照组, 差异有统计学意义(P＜0. 05)。结论 应用危机管理理论可以有效降低儿童口腔科门诊患者投诉事件的发生率, 提升儿童口腔专科护理质量, 有利于促进科室护理工作的健康、稳定发展。)